2022
DOI: 10.1186/s41936-022-00322-6
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and immunohistochemical studies on the influence of orally administration monosodium glutamate, a food additive dependent on time in vivo

Abstract: Background Monosodium glutamate is a widely used flavor enhancer/food additive in meat, fish, milk and cheese or vegetable origins. Our present study aimed to assess the effect of utilization monosodium glutamate on the cardiac, splenic, hepatic and renal organs in mice. Thirty animals were divided into three groups: control group; glutamate 10 treated groups and glutamate 15 treated group. The experimental period was two successive weeks. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
2
0
0
Order By: Relevance
“…These results agreed with those of Hazzaa et al (2020), Hassan et al (2020), andAbo El Wafa et al (2021). The abnormalities might be attributed to MSG-induced oxidative damage (Hamad, 2022), as demonstrated in the present work by a rise in MDA and a reduction in TAC. The oxidative stress triggers the nuclear factor-κB signaling pathway, which can control numerous genes linked to inflammatory responses, including tumor necrosis factor-α and the caspases family, which causes cell death (Hamad, 2022).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These results agreed with those of Hazzaa et al (2020), Hassan et al (2020), andAbo El Wafa et al (2021). The abnormalities might be attributed to MSG-induced oxidative damage (Hamad, 2022), as demonstrated in the present work by a rise in MDA and a reduction in TAC. The oxidative stress triggers the nuclear factor-κB signaling pathway, which can control numerous genes linked to inflammatory responses, including tumor necrosis factor-α and the caspases family, which causes cell death (Hamad, 2022).…”
Section: Discussionsupporting
confidence: 72%
“…The abnormalities might be attributed to MSG-induced oxidative damage (Hamad, 2022), as demonstrated in the present work by a rise in MDA and a reduction in TAC. The oxidative stress triggers the nuclear factor-κB signaling pathway, which can control numerous genes linked to inflammatory responses, including tumor necrosis factor-α and the caspases family, which causes cell death (Hamad, 2022). In addition, CUR-NPS administration alleviated the pathological changes caused by MSG, which is comparable with the findings of , who found that CUR-NPS reduced the histopathological abnormalities created in the hearts of copper sulfate-intoxicated rats.…”
Section: Discussionsupporting
confidence: 72%